Transfert de champs par approximation diffuse avec conservation de l'énergie - Brancherie, Delphine; Villon, Pierre; Ibrahimbegovi´, Adnan; Rassineux, Alain; Breitkopf, Piotr (European Journal of Computational Mechanics, 2006)
In this work, we present a eld transfer operator based on diffuse approximation. The operator is developped for damage materials in small deformations. The key point of the proposed transfer operator is to ensure the conservation of energy between the old and the new discretization.